Evaluation of Essential, Toxic and Potentially Toxic Elements in Leafy Vegetables Grown in the Canary Islands - Verónica Martín-León; Carmen Rubio; Ángel Rodríguez-Hernández; Manuel Zumbado; Andrea Acosta-Dacal; Luis Alberto Henríquez-Hernández; Luis D. Boada; María del Mar Travieso-Aja; Octavio P. Luzardo (Toxics, 2023)
Forty-seven elements in leafy green vegetables were studied to estimate the daily intakes from this food category in different scenarios (average and high consumers) and age groups of the Canary Islands population. The contribution of the consumption of each type of vegetable to the reference intakes of essential, toxic and potentially toxic elements was assessed and the risk–benefit ratio was evaluated. The leafy vegetables that provide the highest levels of elements are spinach, arugula, watercress and chard. While spinach, chard, arugula, lettuce sprouts and watercress were the leafy vegetables with the highest concentrations of essential elements (38,743 ng/g of Fe in spinach, 3733 ng/g of Zn in watercress), the high levels of Mn in chard, spinach and watercress are noteworthy. Among the toxic elements, Cd is the element with the highest concentration, followed by As and Pb. The vegetable with the highest concentration of potentially toxic elements (Al, Ag, Be, Cr, Ni, Sr and V) is spinach. In average adult consumers, while the greatest contribution of essential elements comes from arugula, spinach and watercress, insignificant dietary intakes of potentially toxic metals are observed. Toxic metal intakes from the consumption of leafy vegetables in the Canary Islands do not show significant values, so the consumption of these foods does not pose a health risk. In conclusion, the consumption of leafy vegetables provides significant levels of some essential elements (Fe, Mn, Mo, Co and Se), but also of some potentially toxic elements (Al, Cr and Tl). A high consumer of leafy vegetables would see their daily nutritional needs regarding Fe, Mn, Mo, and Co covered, although they are also exposed to moderately worrying levels of Tl. To monitor the safety of dietary exposure to these metals, total diet studies on those elements with dietary exposures above the reference values derived from the consumption of this food category, mainly Tl, are recommended.